Upaya Guru PAI dalam Meningkatkan Kemampuan Membaca Al Quran Siswa Melalui Program Baca dan Hafal Al Quran (BHQ) di SMPN 1 Batealit - Ahmad Mawahibur Riski; Alex Yusron Al Mufti (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to get a description of efforts to improve the reading ability of students in the Qur'an at SMPN 1 Batealit through the Reading and Memorizing the Qur'an (BHQ) program, the implementation and methods used and the progress felt from each student in each class. The ability of students to read the Qur'an should also be important, even if it is in an educational institution that does not have an Islamic school background such as SMPN 1 Batealit. So that even with limited religious subjects, SMPN 1 Batealit is able to have a program that can improve students' ability to read the Qur'an. The research method used is qualitative descriptive, with the intention of describing the Reading and Memorizing the Qur'an (BHQ) program which is carried out at SMPN 1 Batealit. The data source is the Reading and Memorizing Al Quran (BHQ) program and the person in charge is Mrs. Istiqomah, S.Pd.I. who is also a PAI teacher at SMPN 1 Batealit. Data collection through observation, interviews and then documentation. The findings resulting from this study include; 1. The ability to read the Qur'an of students, and 2. Implementation of the Qur'an Reading & Memorization Program (BHQ) in Improving Students' Qur'an Reading Ability at SMPN 1 Batealit.